Improved depiction of subthalamic nucleus and globus pallidus internus with optimized high‐resolution quantitative susceptibility mapping at 7 T. (20th July 2020) - Cong, Fei; Liu, Xueru; Liu, Chia‐Shang Jason; Xu, Xin; Shen, Yelong; Wang, Bo; Zhuo, Yan; Yan, Lirong
Abstract : The subthalamic nucleus (STN) and globus pallidus internus (GPi) are commonly used targets in deep‐brain stimulation (DBS) surgery for the treatment of movement disorders. The success of DBS critically depends on the spatial precision of stimulation. By taking advantage of good contrast between iron‐rich deep‐brain nuclei and surrounding tissues, quantitative susceptibility mapping (QSM) has shown promise in differentiating the STN and GPi from the adjacent substantia nigra and globus pallidus externus, respectively. Nonlinear morphology‐enabled dipole inversion (NMEDI) is a widely used QSM algorithm, but the image quality of reconstructed susceptibility maps relies on the regularization parameter selection. To date, few studies have systematically optimized the regularization parameter at the ultra‐high field of 7 T. In this study, we optimized the regularization parameter in NMEDI to improve the depiction of STN and GPi at different spatial resolutions at both 3 T and 7 T. The optimized QSM images were further compared with other susceptibility‐based images, including T 2*‐weighted (T2*w), R 2*, susceptibility‐weighted, and phase images. QSM showed better depiction of deep‐brain nuclei with clearer boundaries compared with the other methods, and 7 T QSM at 0.35 × 0.35 × 1.0 mm 3 demonstrated superior performance to the others. Our findings suggest that optimized high‐resolution QSM at 7 T allows for improved delineation of deep‐brain nuclei with clear and sharp borders between nuclei, which may become a promising tool for DBS nucleus preoperative localization. Abstract : The regularization parameter in NMEDI was optimized for the depiction of STN and GPi at different spatial resolutions at 3 T and 7 T. Our results suggest that the optimal regularization parameter decreases with increased spatial resolution and increases from 3 T to 7 T. Compared with the other susceptibility‐based imaging methods, optimized QSM, especially 7 T high‐resolution QSM, allows for improved delineation of deep‐brain nuclei with clear and sharp borders.